2017
DOI: 10.1016/j.cmet.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis in Brown Adipocytes Is Not Essential for Cold-Induced Thermogenesis in Mice

Abstract: Summary Lipid droplet (LD) lipolysis in brown adipose tissue (BAT) is generally considered to be required for cold-induced nonshivering thermogenesis. Here we show that mice lacking BAT Comparative Gene Identification-58 (CGI-58), a lipolytic activator essential for the stimulated LD lipolysis, have normal thermogenic capacity and are not cold sensitive. Relative to littermate controls, these animals had higher body temperatures when they were provided food during cold exposure. The increase in body temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
203
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(232 citation statements)
references
References 65 publications
18
203
5
1
Order By: Relevance
“…Conversely, there is also evidence that lipolysis is not energetically critical for heat production in BAT. Others have observed that in the absence of BAT lipolysis during cold acclimation, thermoregulation is supported by iWAT lipolysis under fasting conditions or by diet nutrients [34]. However, in our study, long-term cold challenge had no effect on iWAT weight.…”
Section: Demonstrated Thatcontrasting
confidence: 88%
See 1 more Smart Citation
“…Conversely, there is also evidence that lipolysis is not energetically critical for heat production in BAT. Others have observed that in the absence of BAT lipolysis during cold acclimation, thermoregulation is supported by iWAT lipolysis under fasting conditions or by diet nutrients [34]. However, in our study, long-term cold challenge had no effect on iWAT weight.…”
Section: Demonstrated Thatcontrasting
confidence: 88%
“…Cooling sensitivity is the first step to activate the cold response neuronal mechanism that modulates lipolysis and energy expenditure [34]. Cold-induced metabolic changes are more pronounced in BAT compared to WAT depots [35].…”
Section: Demonstrated Thatmentioning
confidence: 99%
“…Thereto, mice treated with a A 2A agonist exhibit increased energy expenditure as well as resilience to the effects of high-fat diet feeding as illustrated by improved glucose tolerance and a leaner phenotype than control mice [51]. In brown and beige adipocytes, lipolysis is central, but not indispensable, for thermogenesis and Ucp1dependent uncoupling [52][53][54][55].…”
Section: Browning/beiging Signalsmentioning
confidence: 99%
“…The process of lipolysis that generates FFA is thus crucial for normal thermogenesis (Himms-Hagen, 1972). Furthermore, it has been shown that lipolysis in white adipocytes is required to fuel NST (Schreiber et al, 2017;Shin et al, 2017). Several features of the Opn3 germ-line and "minus blue" mice suggested there might be a defect in thermogenesis: In inWAT, Ucp1 transcripts and protein are at low levels, there is low "brite" adipocyte and NAD content and similarly, in iBAT, UCP1 and some ETC complex proteins are at low levels.…”
Section: Adaptive Thermogenesis In Mice Is Promoted By Blue Light Inmentioning
confidence: 99%
“…The long-standing belief that BAT lipolysis is essential for non-shivering thermogenesis has been challenged by recent analysis (Schreiber et al, 2017;Shin et al, 2017). These investigators showed that inhibiting lipolysis in BAT does not impair body temperature maintenance as long as thermogenic fuel was available through WAT lipolysis or dietary sources.…”
Section: White Adipocyte Opn3 Is Required For Normal Lipolysis Duringmentioning
confidence: 99%